Multivariate analysis on performance in statistics, self-efficacy and attitudes of senior high school students - Mildin Jeminez Retutas; Marilyn Torela Rubio (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2021)
Over the past few years, teaching and learning of statistics have been influenced by the emergence of the reform movement in education such as the K-12 basic education curriculum. Those of statistics concepts have changed both elementary and secondary level. Considering the educational reform in the Philippines, the study was conducted to determine whether there are significant differences of the determinants such as gender, type of school, parent’s educational level, family monthly income, family size and Senior High School track preference to students’ self-efficacy beliefs, attitudes towards Statistics, and performance in Statistics. The causal-comparative research design was used for comparing two or more groups to find the differences or determine whether the independent variable influences the dependent variable. The data were gathered from 570 senior high school students of both public and private schools in Mindanao, Region XI. The study adopted the questionnaires on self-efficacy beliefs and attitude towards Statistics while it utilized a researcher-made questionnaire for performance in Statistics. Multivariate Analysis of Variance (MANOVA) was used to determine whether multiple levels of independent variables on their own or in combination with one another influence the dependent variables. The findings revealed that among the demographic factors, only type of school has a significant difference to the self-efficacy beliefs, attitudes towards Statistics, and performance of senior high students in Statistics. Implications from the findings of this study might suggest that improving of K-12 school facilities by the school public administrators and collaborative effort of teachers to enhance the students’ self-efficacy, attitudes towards statistics and teaching statistics reveals optimistic results. Also, school administrators may provide opportunities for Statistics teachers to hone their pedagogical skills in promoting and building students’ self-confidence and interest in the subject.